2023
DOI: 10.1038/s41467-023-36626-6
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin-D activation promotes NLRP3 activation and host resistance to Leishmania infection

Abstract: Intracellular parasites from the Leishmania genus cause Leishmaniasis, a disease affecting millions of people worldwide. NLRP3 inflammasome is key for disease outcome, but the molecular mechanisms upstream of the inflammasome activation are still unclear. Here, we demonstrate that despite the absence of pyroptosis, Gasdermin-D (GSDMD) is active at the early stages of Leishmania infection in macrophages, allowing transient cell permeabilization, potassium efflux, and NLRP3 inflammasome activation. Further, GSDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…Previous studies have shown that pyroptosis and inflammasome activation are separable processes and that myeloid cells can release IL-1β over time without undergoing pyroptosis. 38, 39, 41 One such study showed that oxidized phospholipids can enhance IL-1β release without inducing cell death through engagement of CD14 in macrophages and dendritic cells. 63 Since DENV NS1 is secreted from infected cells as an oligomer surrounding a lipid cargo, we hypothesized that DENV NS1 might also enhance IL-1β release by delivering lipids to cells in a CD14-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that pyroptosis and inflammasome activation are separable processes and that myeloid cells can release IL-1β over time without undergoing pyroptosis. 38, 39, 41 One such study showed that oxidized phospholipids can enhance IL-1β release without inducing cell death through engagement of CD14 in macrophages and dendritic cells. 63 Since DENV NS1 is secreted from infected cells as an oligomer surrounding a lipid cargo, we hypothesized that DENV NS1 might also enhance IL-1β release by delivering lipids to cells in a CD14-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…36 The formation of GSDMD pores canonically leads to pyroptosis, a form of inflammatory cell death; however, recent work has shown that GSDMD pore formation and pyroptosis are distinct events and that macrophages can release IL-1β from GSDMD pores without undergoing pyroptosis in response to certain stimuli. [37][38][39][40][41] GSDMD pores also facilitate the release of cleaved IL-1β and IL-18, which then serve as major mediators of inflammation contributing to host defense as well as driving immunopathology. 37,42 Many viruses have been shown to activate inflammasomes during infection, including influenza A virus, HIV, SARS-CoV-2, picornaviruses, and DENV.…”
Section: Introductionmentioning
confidence: 99%
“…Jurkat cells (ATCC) were labeled with 1µM Calcein for 1 hour and washed with PBS 3 times. Calcein labeled cells were treated with 1µM of staurosporine for (16)(17)(18)(19)(20) hours to induce apoptosis. After 16 hours of treatment, apoptosis was confirmed by looking at the membrane blebbing of the cells under confocal microscope.…”
Section: Mice and Dietsmentioning
confidence: 99%
“…GsdmD can be cleaved via capase-1/Nlrp3 dependent canonical inflammasome pathway, or via a caspase-11 (in mice) or caspase-4/5 (in humans) dependent non-canonical inflammasome pathway. The NT-GsdmD fragment generated via non-canonical pathway can in-turn activate the canonical inflammasome in a positive feedback loop 18 . GsdmD thus serves as a common executor of both canonical and non-canonical pyroptosis [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in bladder cancer, USP24 stabilizes the nonpyroptotic GSDMB isoform, which enhances STAT3 phosphorylation and promotes cancer cell proliferation [120]. In response to pathogenic bacteria invading the host, GSDMs quickly execute pyroptosis in infected cells such as epithelial cells, neutrophils, and macrophages to prevent intracellular pathogen replication [23,28,[121][122][123]. However, certain microorganisms have developed specific mechanisms to counteract pyroptosis [124,125] (Figure 3,4).…”
Section: Ubiquitination and Deubiquitinationmentioning
confidence: 99%